A genetic coding variant rs72474224 in GJB2 is associated with clinical features of psoriasis vulgaris in a Chinese Han population. Issue 2 (24th June 2015) - Yao, F.; Yue, M.; Zhang, C.; Zuo, X.; Zheng, X.; Zhang, A.; Wang, Z.; Liu, S.; Li, H.; Meng, L.; Zeng, M.; Fan, X.; et al.
Abstract Our recent targeted sequencing study identified a missense single‐nucleotide polymorphism rs72474224 (c.324C>T) in GJB2. To investigate the correlation between rs72474224 (c.324C>T) and subphenotypes of psoriasis, genotype data for rs72474224 (c.324C>T, p.Val37Ile) was analyzed in 9946 cases and 9906 controls. The additive model provided the best fit for rs72474224 (P = 7.34 × 10−9). The genotypic and allelic frequency distributions were associated with plaque psoriasis in case‐only (Pgenotype = 2.67 × 10−3, Pallele = 6.22 × 10−4) and subphenotype‐control (Pgenotype = 1.58 × 10−11, Pallele = 8.16 × 10−12) analyses. No other significant difference was found in case‐only analyses. Rs72474224 in GJB2 is preferentially associated with plaque psoriasis in Chinese population and might contribute to the complexity of psoriasis clinical features.